The Role of Mediation Intensity Utilization of Academic Information System and Ease of the Use on Task-Technology Fit Influence on Individual Performance (Empirical Study At Mercu Buana University, Yogyakarta) - Djaelani Susanto (Jurnal Perilaku dan Strategi Bisnis, 2021)
This study aims to examine : 1) Influence of Task Technology Fit on Individual Performance, 2) Influence of Task Technology Fit to Intensity of SIA utilization, 3) Influence of Intensity of SIA utilization on individual performance, 4) Effect of SIA utilization intensity to ease of the use, 5) Influence of ease of the use to Individual Performance, 6) Influence of ease of the use as mediator between utilization of academic information system on individual performance. Respondents of this study are the Lecturers and Employees at the University of Mercu Buana Yogyakarta and obtained respondents as many as 113 respondents. This research uses survey model and purposive sampling method as sampling technique. In addition, this research also uses Structural Equation Modeling analysis technique with LISREL as an analytical tool. Based on data testing result of this research, it is found that: 1) Task Technology Fit has influence on Individual Performance, 2) Task Technology Fit has influence onIntensity of SIA Utilization, 3) Intensity of SIA utilization has influence on Individual Performance through ease of the use 4 ) Intensity of SIA utilization has influence on Ease of the Use 5) Ease of the Use has an effect on Individual Performance.